Evolution of Cochlear implant mapping and vestibular function in a pediatric case of Labyrinthitis - Sophie Lipson; Ross O’Shea; Susan Gibbons; Guangwei Zhou; Jacob Brodsky (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Vestibular symptoms such as vertigo and imbalance are known to occur in some cochlear implant patients during the immediate postoperative period; however, acute vertigo in implanted children occurring remotely from the postoperative period has not been previously well-described. Case presentation A three-year-old girl with a history of bilateral sequential cochlear implantation presented with acute labyrinthitis associated with sudden onset of vertigo, balance impairment, and decline in right cochlear implant function 2 years after her most recent implant surgery. We describe her audiological and vestibular testing results during both the acute phase and following medical management and recovery. Conclusion Acute labyrinthitis should be considered when sudden onset vertigo and/or imbalance presents in children with cochlear implants outside of the perioperative period. Such symptoms should prompt early assessment of cochlear implant function, so that the device can be reprogrammed accordingly.